Sungura music’s development in Zimbabwe: the emergence of trendsetters, emulators and copycats - Muranda, Richard; Maguraushe, Wonder (The Journal of Music and Meaning, 2022)
Violation of copyright law has caused quite a stir in Zimbabwe's Sungura 1 music performance. Some prominent musicians accuse upcoming artistes of illegally copying their music, although the popular musicians themselves developed it by modeling on foreign popular musicians' songs, which were on the local market and shows in Zimbabwe. By tracing the development of sungura from the 1960s to contemporary times using a diffusionist paradigm, this paper exposes how sungura artists have developed a genre that owes its popularity to record companies' policies, the media as well as the sungura artists' virtuosity in fusing foreign musical genres (especially Congolese, Kenyan, Tanzanian and South African) and local indigenous traditional styles (mhande, mbende, jiti, shangara). We interviewed sungura artists, recording company personnel and music promoters to elicit their views on the major influences on the development of museve. 2 Based on insights drawn from musical ethnography, the paper goes on to propose a revised framework of analysis and terminology to account for sungura musicians' relationships. We examine the characteristics of a couple of sungura musicians with a view to justifying how each falls into a particular category. Using critical African cultural studies, we proffer the terms trendsetters 3 , emulators 4 and copycats 5 as categories into which sungura musicians in Zimbabwe fit. One way or the other there is mimicry which might account for lack of lawsuits against perceived violators of copyright law. The conclusion suggests collaboration to reform sungura musicians' connections which we think holds potential to propel them to greater success.